Plan integral de mantenimiento preventivo en las instalaciones del museo arte contemporaneo-maczul - Ramírez, Leonardo; Sanchéz, Miguel; Perozo, Alberto (Revista ALCONPAT, 2011)
The preservation of infrastructure for museums must consider the specific conditions and needsduring the service life of the building. This works shows the preparation of the methodologicalbasis for an integral model for the maintenance of the Contemporary Art Museum of Zulia(MACZUL), which includes the preservation of the external aesthetic features, the systems thatsupport its functions, and the exhibition areas. The development of the model and the proposedtool of support allows the formulation of an agile system to set up an administrative structure forthe information management for the maintenance plan. The environmental conditions requirespecial attention with regards to the soundness of the structure, as these favor corrosion process.